2018
DOI: 10.1055/s-0038-1642028
|View full text |Cite
|
Sign up to set email alerts
|

Early Autologous Blood-Patch Pleurodesis versus Conservative Management for Treatment of Secondary Spontaneous Pneumothorax

Abstract: Early intrapleural instillation of autologous blood is successful in sealing air leak in patients with SSP with persistent air leak, who are not fit or not willing to undergo surgery. It is superior to conservative treatment or late instillation of autologous blood, even if their lungs are not fully expanded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Recently, early BPP trials at 48 and 72 h for treatment of pneumothorax have been reported in human medicine. 19,30 Financial considerations may also dictate attempts at BPP in human and veterinary medicine. 19 BPP was elected in the cats reported herein based on severe, continuous pneumothorax necessitating continuous suction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, early BPP trials at 48 and 72 h for treatment of pneumothorax have been reported in human medicine. 19,30 Financial considerations may also dictate attempts at BPP in human and veterinary medicine. 19 BPP was elected in the cats reported herein based on severe, continuous pneumothorax necessitating continuous suction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in adult human medicine autologous BPP recommendations include the use of 50–100 ml total (roughly ⩽1 ml/kg). 17 , 18 , 30 Studies have reported that higher blood volumes (100 ml or 1–2 ml/kg) had more rapid resolution of continuous pneumothorax than lower blood volumes (50 ml). 11 , 16 In children, the volume of fresh whole blood for BBP has been reported and ranged from 1 to 2.5 ml/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autologous blood application and pleurodesis are safe, easy, cheap and effective methods. [7,8] It should be considered in cases where the full expansion of the lung cannot be achieved. [8] Indeed, bronchial air leakage can be corrected by creating a fibrin plug within minutes with autologous blood.…”
Section: Discussionmentioning
confidence: 99%
“…phlebotomizing 50-100 mL of peripheral venous blood followed by its instillation through an existing tube thoracostomy (34). The chest tube is then flushed and clamped or elevated to permit adequate dwell time.…”
Section: A U T O L O G O U S B L O O D P a T C H P L E U R O D E S I S I N V O L V E Smentioning
confidence: 99%